2020
DOI: 10.1371/journal.pone.0237244
|View full text |Cite
|
Sign up to set email alerts
|

Is pre-operative heart rate variability a prognostic indicator for overall survival and cancer recurrence in patients with primary colorectal cancer?

Abstract: Background Heart Rate Variability (HRV) represents efferent vagus nerve activity which is suggested to be inversely related to fundamental mechanisms of tumorigenesis and to be a predictor of prognosis in various types of cancer. HRV is also believed to predict the occurrence and severity of post-operative complications. We aimed to determine the role of pre-operative HRV as a prognostic factor in overall and cancer free survival in patients with colorectal cancer. Methods Retrospective analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Scheffler et al [ 77 ] did not find a correlation between preOP HRV (time and frequency domain analysis) and postOP complications (leaks, infections, and thrombosis) after abdominal surgery. Strous et al did not find a correlation between HRV (SDNN and rMSSD) and occurrence or severity of postOP complications in colorectal cancer surgery [ 78 ]. Ernst et al [ 50 ] found that lower rMSSD (p < 0.05) predicted occurrence of overall complications (death, pneumonia, urinary tract infection, myocardial infarction, and stroke) and lower VLF predicted infections (p < 0.05) in hip fracture patients.…”
Section: Resultsmentioning
confidence: 99%
“…Scheffler et al [ 77 ] did not find a correlation between preOP HRV (time and frequency domain analysis) and postOP complications (leaks, infections, and thrombosis) after abdominal surgery. Strous et al did not find a correlation between HRV (SDNN and rMSSD) and occurrence or severity of postOP complications in colorectal cancer surgery [ 78 ]. Ernst et al [ 50 ] found that lower rMSSD (p < 0.05) predicted occurrence of overall complications (death, pneumonia, urinary tract infection, myocardial infarction, and stroke) and lower VLF predicted infections (p < 0.05) in hip fracture patients.…”
Section: Resultsmentioning
confidence: 99%
“…These depend very much on the duration of HRV analysis. On the other hand, a recent study published by Strous MTA et al highlighted the fact that HRV was found to have no prognostic value in patients with primary colorectal cancer who underwent curative surgical treatment because low HRV indices were not associated with reduced overall survival [ 27 ]. Moreover, low HRV was not significantly associated with elevated CEA levels during follow-up or postoperative complications [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study published by Strous MTA et al highlighted the fact that HRV was found to have no prognostic value in patients with primary colorectal cancer who underwent curative surgical treatment because low HRV indices were not associated with reduced overall survival [ 27 ]. Moreover, low HRV was not significantly associated with elevated CEA levels during follow-up or postoperative complications [ 27 ]. The duration of HRV analysis was only 10 s because, in that study, only standard electrocardiograms were used for HRV analysis, which records cardiac electrical activity for only 10 s. In comparison, the duration of HRV analysis in our study was between 20 and 30 h. Other cancers in which the prognostic value of HRV reduction was analyzed were pancreatic cancer [ 17 ], prostate and non-small cell lung cancer [ 28 ], and gastric cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methods for quantitative analysis of HRV are mainly based on linear methods in the time and frequency domains and nonlinear methods. Existing studies on the relationship between the time- and frequency-domain parameters of HRV and the prognosis of many kinds of malignant tumors, such as liver cancer ( Chiang et al, 2010 ), pancreatic cancer ( De Couck et al, 2016 ), BM ( Wang et al, 2013 ; Wang et al, 2021 ), colorectal cancer ( Strous et al, 2020 ) and LCBM ( Wu et al, 2022 ), have shown that a low level of linear HRV is associated with poor prognosis of cancer patients, which is of great significance for the formulation of treatment strategies for cancer patients.…”
Section: Introductionmentioning
confidence: 99%